Investigating Translation Strategies of Lyrics: A Case Study of English and French Versions of the Song Unstoppable by Sia and Sara’h - DADJO, Servais Dieu-Donné Yédia (My University, 2023)
This paper investigates the translation strategies used while translating Sia’s lyrics intitled Unstoppable into French. It aims at identifying the translation strategies used while translating the selected lyrics into French in order to determine the most suitable strategies for lyrics translation on the one hand and provide a new interpretation for the selected lyrics on the other hand. The theories that underpin this work are Levefere (1975)’s strategies of poetry translation and Baker (1992)’s strategies for non-equivalence at word level. A mixed method has helped the researcher identify and analyze the translation strategies used in the French version of the selected lyrics. The study reveals different proportions of translation strategies: metrical translation 42%, interpretation 38%, rhymed translation 8%, phonemic translation 8% and literal translation 4% following Levefere (1975)’ theory on the one hand. On the other hand, the study reveals following Baker (1992)’s theory, paraphrase using related words 58%, paraphrase using unrelated words 25% and omission 17%. It has been observed that metrical translation strategy is the most suitable for song translation since the translator needs to respect not only the original meter and rhythm but also the melody. This explains the high use of metrical translation strategy. The strategy of interpretation helps the translator create new forms in the target language basing on her own understandings, cultures and styles for the purpose of conveying adapted meanings from the original ones.
Keywords: Interpretation; Meter; metrical; translation; phonemic; rhymed; translation.